2020
DOI: 10.15294/jpii.v9i2.23349
|View full text |Cite
|
Sign up to set email alerts
|

The Interpreting Ability on Science Kinematics Graphs of Senior High School Students in South Sulawesi, Indonesia

Abstract: This research was a descriptive case study. The purpose of this research was to describe the student’s ability to interpret the kinematics graph. The subjects of the study were 347 students of class XI science in the even semester of 2018/2019 in Luwu Raya, South Sulawesi Province, Indonesia. The research data were obtained from multiple-choice test results using instruments adapted from Test of Understanding Graph – Kinematics 2.6 and the results of in-depth interviews to find out the reasons learners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 20 publications
(24 reference statements)
0
21
0
15
Order By: Relevance
“…The first category includes difficulties with discriminating between slope and height, interpreting changes in height and changes in slope, and interpreting the area under a graph curve, for example. Confirmations of the existence of these difficulties can be found in the papers by [8,[24][25][26], etc. According to [24], the area under a curve is a difficult concept for students; therefore, more attention should be given to this.…”
Section: Students' Achievement On the Knowledge Testmentioning
confidence: 73%
See 2 more Smart Citations
“…The first category includes difficulties with discriminating between slope and height, interpreting changes in height and changes in slope, and interpreting the area under a graph curve, for example. Confirmations of the existence of these difficulties can be found in the papers by [8,[24][25][26], etc. According to [24], the area under a curve is a difficult concept for students; therefore, more attention should be given to this.…”
Section: Students' Achievement On the Knowledge Testmentioning
confidence: 73%
“…One of the physics topics that abounds in graphs is kinematics. Kinematics includes the concepts of position, displacement, velocity, speed, and acceleration and discusses straight motion without considering the causes of motion, defined as forces [8]. Position vs. time, velocity vs. time, and acceleration vs. time are the three main kinematics graphs [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies (Antwi, Savelsbergh, & Eijkelhof, 2018;Ivanjek, Susac, Planinic, Andrasevic, & Milin-Sipus, 2016;Maries & Singh, 2013;Planinic, Ivanjek, & Susac, 2013;Vaara & Sasaki, 2019;Zavala et al, 2017) have reported that students have difficulty in understanding kinematics graphs, changing from one kinematics graphs to another, calculating and interpreting an area, comprehending the meaning of the slope of a line, determining the height of a point on the line, relating graphs to physics concepts, interpreting curved graphs differently from rectilinear graphs, making a connection between graphs and a particular subject, identifying specific events in graphs of velocity-time, acceleration-time, and position-time, analyzing deceleration and acceleration. Some studies (Amin et al, 2020;Bektaslı & White, 2012) have found that many students have great difficulty in reading kinematic graphs, so there is a close relationship between logical thinking and the skill to interpret kinematics graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Kinematics is a part of physics that deals with motion without considering the causes (forces) [1]. This topic is one of the fundamental topics because it has a big role in the construction of concepts in other physics topics.…”
Section: Introductionmentioning
confidence: 99%